Moderate Consumption of Freeze-dried Blueberry Powder Increased Net Bone Calcium Retention in Healthy Postmenopausal Women: A Randomized Crossover Trial. (29th May 2020) - Hodges, Joanna; Cao, Sisi; Lachcik, Pamela; Peacock, Munro; McCabe, George; McCabe, Linda; Cladis, Dennis; Ferruzzi, Mario; Martin, Berdine; Weaver, Connie
Abstract: Objectives: Preclinical studies suggest that blueberry consumption is associated with improved bone health. This study quantified changes in urinary excretion of the long-lived calcium radioisotope 41 Ca to assess the dose-response effect of blueberries on bone loss in postmenopausal women. We hypothesized that blueberry consumption would reduce bone loss in a dose-dependent manner. Methods: Healthy women at least 4 years past menopause were dosed with 50 nCi of 41 Ca and completed a 5-mo equilibration period for 41 Ca deposition in bone followed by a 6-wk control period. Subsequently, participants were assigned to a random sequence of 3 intervention periods, each corresponding to a low (17.5 g/d), medium (35 g/d), or high (70 g/d) dose of freeze-dried blueberry powder equivalent to 0.75, 1.5, or 3 cups of fresh blueberries. The blueberry powder was incorporated into granola bars, spread, and drinks consumed daily for 6 wk, followed by a 6-wk washout period. Urinary 41 Ca: Ca ratio was measured by accelerator mass spectrometry in 24-h urine collected weekly during intervention and every 3 wk during washout. Serum 25-hydroxyvitamin D and calcium concentrations were assessed prior to each intervention. Serum bone resorption biomarkers and urinary polyphenols were measured at the end of each control and intervention period. Data were analyzed using a linear mixed model and repeated measures ANOVA. Results: Fourteen healthy, non-osteoporotic (mean bone mineral density t-score: −1.33) women completed the study. Net bone calcium retention increased by 6% in the low ( P < 0.01) and 4% in the medium ( P < 0.05) dose intervention compared with the control and washout periods. The high dose had no significant effect on net bone calcium retention ( P  = 0.19). Urinary excretion of hippuric acid increased dose-dependently with blueberry consumption. No significant relationships were found between bone resorption biomarkers, 25-hydroxyvitamin D, or calcium and any of the interventions. Conclusions: A hormetic response was observed to blueberry intake, whereby daily consumption of foods containing 17.5–35 g, but not 70 g, of freeze-dried blueberry powder increased net bone calcium retention. Moderate consumption of blueberries may be an effective strategy to attenuate bone loss in healthy postmenopausal women. Funding Sources: NIH/NCCIH, Project Development Team within the ICTSI NIH/NCRR.